Unilever Company Work Model - Hamidah binti Tsuraya; Lia Endayani; Fazila Monivatu Zahda; Isti Shintya Utami; Usman Jayadi (International Journal of Economics, Management and Accounting (IJEMA), 2023)
Working capital is the amount of cash and current assets available to cover the day-to-day operating expenses of a company. In the context of Unilever, working capital includes inventories, receivables and debts used to maintain smooth operations, meet financial obligations and maintain adequate liquidity. Unilever uses working capital to finance the purchase of raw materials, manage inventory, and fulfill payment obligations from customers. Good working capital management enables Unilever to control liquidity risk, improve operational efficiency, and maintain adequate funds available to carry out daily activities. In practice, Unilever must carry out efficient inventory management, manage receivables properly, and use debt wisely to meet working capital needs. With good working capital management, Unilever can maintain healthy financial performance, minimize liquidity risk, and take advantage of growth opportunities. Effective working capital plays an important role in maintaining the smooth operation of the company and achieving short- and long-term goals. In Unilever's case, well-managed working capital enables the company to meet market demands, maintain high levels of service, and gain a competitive advantage in the consumer product industry. In order to maintain sustainability and growth, Unilever must continue to carefully monitor and manage working capital, optimize its use, and take appropriate measures to ensure adequate liquidity in carrying out its business operations in Indonesia and around the world. Overall, Unilever generates significant profits from its businesses around the world. Despite a decline in net profit in 2020, the company has recorded strong profit growth in recent years, particularly from markets in Asia, Africa, the Middle East and Latin America. Unilever's well-known brands also remain important contributors to the company's revenue and profit growth.